Bentuk-Bentuk Pemberdayaan Ekonomi pada Pondok Pesantren Modern Al Muttaqien Balikpapan - Muhammad Irawan; Darmawati Darmawati; Nurul Fadhilah; Yovanda Noni (Borneo Islamic Finance and Economics Journal, 2022)
The concept of pesantren economic empowerment carried out by the Al Muttaqien Islamic Boarding School in Balikpapan is the ability and skill of the pesantren in utilizing its potential and efforts to run a business process through business units. With the aim of creating a spirit of independence for Islamic boarding schools. Therefore, this study aims to find out what forms of economic empowerment are carried out by the Al Muttaqien Islamic boarding school in Balikpapan, as well as to find out what the benefits of economic empowerment are to the operational continuity of the pesantren, and to find out the supporting and inhibiting factors. Methodologically, this research uses qualitative research procedures. By using this type of descriptive research. As for data collection techniques using observation, interviews and documentation. And the data analysis techniques used are the reduction of data, the presentation of data and the drawing of conclusions. Al Muttaqien Islamic boarding school has various forms of economic empowerment working out a unit that is owned: a general contractor & carrier, tour & travel, convection & benefit and sharia cooperative gift Al Muttaqien. There are several benefits successfully achieved from the economic empowerment activity of the boarding house, namely: subsidies on unemployment (SPP) for santri cannot afford, build tools or facilities in order to support the activities of the boarding house and improve the welfare of teachers/employees. Key words: Empowerment, Economics, Boarding School